Pengaruh Etos Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan di CV Sanli Kediri - Dila Oktaviani; Sasi Utami; Yogi Yunanto; Katherin Daniar (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the extent to which work ethic and work environment influence employee performance at CV Sanli Kediri. A quantitative research approach was employed, involving the entire population of 30 employees as the sample through a saturated sampling technique. The data collected were analyzed using multiple linear regression analysis. The findings reveal that both work ethic and work environment, whether assessed individually or jointly, have a positive and significant effect on employee performance. The t-test results for the work ethic variable show a t-value of 2.932, which exceeds the critical t-table value of 1.697. Meanwhile, the work environment variable with a t-value of 8.864, also surpassing the t-table value of 1.679. From these results, it can be concluded that improving employees’ work ethic and establishing a supportive work environment have a tangible impact that contributes to enhancing employee performance. This highlights the importance of simultaneously managing both factors to sustain employee productivity.